A naturally occurring alternative product of the mastermind locus that represses notch signalling. - Giráldez, A.J.; Pérez, L.; Cohen, S.M. (Mechanisms of Development, 2002)
The mastermind locus encodes a nuclear protein required in the Notch signalling pathway. In a screen for genes affecting wing pattern, we identified an EP element that directs expression of an alternatively spliced form of the mastermind transcript that we call mam[DN]. Unlike the conventional mam transcript, mam[DN] is spatially regulated in the developing embryonic nervous system and eye imaginal disc. mam[DN] corresponds to an endogenous transcript and encodes an alternate form of the Mam protein that dominantly interferes with activity of the conventional Mam protein. Mam[DN] blocks Notch signalling downstream from the activated form of Notch but cannot interfere with an activated form of Su(H), suggesting that Mam[DN] may interfere with the activity of a ternary complex involving Mam, Notch and Su(H).